2013
DOI: 10.1007/s12011-013-9783-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Trace Metal Concentrations (Co, Cu, Fe, Mn, Zn, Cd, and Ni) in Whole Blood, Plasma, and Urine of Obese and Nonobese Children

Abstract: High-performance ion chromatography and inductively coupled plasma–mass spectrometry methods have been applied to estimate the content of Cd, Co, Cu, Fe, Mn, Zn, and Ni in whole blood, plasma, and urine of obese and nonobese children. The study was conducted on a group of 81 Polish children of age 6–17 years (37 males, 44 females). Obese children were defined as those with body mass index (BMI) >95th percentile in each age–gender-specific group. Statistical testing was done by the use of nonparametric tests (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 46 publications
6
49
0
1
Order By: Relevance
“…A lack of Zn in the body leads to a number of disorders associated with obesity [61]. In addition, changes in zinc levels in the body are a marker of various inflammatory processes, including obesity [62,63]. In our experiment, we observed a recovery of Zn levels in the DIO + DDW group to those of the Control + MilliQ group.…”
Section: Discussionsupporting
confidence: 53%
“…A lack of Zn in the body leads to a number of disorders associated with obesity [61]. In addition, changes in zinc levels in the body are a marker of various inflammatory processes, including obesity [62,63]. In our experiment, we observed a recovery of Zn levels in the DIO + DDW group to those of the Control + MilliQ group.…”
Section: Discussionsupporting
confidence: 53%
“…The artificial urine recipe was prepared according to Shiotsuki et al 22 (Table S1, SI). Zn, Cd and Se with natural isotopic compositions were also added into the solution to obtain the average concentrations found in human urine of 650, 0.2 and 40 ppb, respectively [11][12][13] .…”
Section: Methodsmentioning
confidence: 99%
“…650, 0.2 and 40 ppb of Zn, Cd and Se and human blood plasma contains ca. 1000, 0.3 and 100 ppb, respectively [11][12][13] . Therefore, during fate and/or toxicity studies, it is crucial to distinguish the trace metals naturally present in the matrix from the ones originated from the QDs.…”
mentioning
confidence: 99%
“…No report of cobalt deficiency in normal individuals fed a balanced diet has been documented. However, it has been reported that obese children might have abnormally low levels of Co in their blood and may need supplementation [66].…”
Section: Exposure and Metabolism Of Comentioning
confidence: 99%